2017
DOI: 10.1007/s00330-017-4975-9
|View full text |Cite
|
Sign up to set email alerts
|

Controversies on lung cancers manifesting as part-solid nodules

Abstract: Purpose Summarise survival of patients with resected lung cancers manifesting as part-solid nodules (PSNs). Methods PubMed/MEDLINE and EMBASE databases were searched for all studies/clinical trials on CT-detected lung cancer in English before 21 December 2015 to identify surgically resected lung cancers manifesting as PSNs. Outcome measures were lung cancer-specific survival (LCS), overall survival (OS), or disease-free survival (DFS). All PSNs were classified by the percentage of solid component to the enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 94 publications
1
44
0
Order By: Relevance
“…34,35,38 In fact, delayed resection of SSN until signs of growth did not increase mortality in our series, validating the retrospective evidence from previous studies. 8,30,31,35,39 The conservative management of SSNs preserved the lung function in subjects that subsequently required resection of more aggressive cancer in other pulmonary sites. Early SSN resection could have caused deterioration of pulmonary function and quality of life, potentially hampering resectability of a second more aggressive lung cancer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…34,35,38 In fact, delayed resection of SSN until signs of growth did not increase mortality in our series, validating the retrospective evidence from previous studies. 8,30,31,35,39 The conservative management of SSNs preserved the lung function in subjects that subsequently required resection of more aggressive cancer in other pulmonary sites. Early SSN resection could have caused deterioration of pulmonary function and quality of life, potentially hampering resectability of a second more aggressive lung cancer.…”
Section: Discussionsupporting
confidence: 90%
“…34 A systematic review of the literature on slow-growing adenocarcinoma derived from SSNs showed that the proportion of the solid component, but not the total size of the SSN, correlates with outcome measures, supporting a conservative management of slow growing tumors. 35 The long-term outcome of subjects with SSNs from the MILD trial shows that it is a safe option to manage SSNs conservatively until signs of growth of the solid component. Although only a minority of SSNs were resected under the MILD protocol (8 of 389 including one protocol violation), none of the unresected persistent SSNs developed into a clinically perceivable cancer within the follow-up period of almost 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested a clear definition of the upper limit of the solid component of PSNs. 6 In 2017, Matsunaga et al divided part-solid lung cancers into ground glass-predominant and consolidation-predominant tumors, with a cutoff value 0.5 for the consolidation-to-tumor (CTR) ratio. They found that PSNs with a CTR of 0.5 or higher had a higher prevalence of lymphatic invasion and worse 5-year recurrence-free survival (RFS) than those with a CTR less than 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…Extremely rare lymph node metastasis and 100% 5-year survival have been reported for NSNs [101]. For NSNs, size of the solid component (>5 mm), its ratio to total nodule size (⩾80%) and its evolution can be used to minimise the rate of overdiagnosis [67,102].…”
Section: Overdiagnosis and Harmsmentioning
confidence: 99%